Maize Production and Food Security in Garu District of Upper East Region, Ghana - Bawa, Alhassan; Asampambila, Denis (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2022)
Agriculture is the dominant occupation in the Garu district that employs over 95 percent of households. However, yields of maize in the district are perpetually low. This might be due to intermittent drought (erratic rainfall pattern), low soil fertility, invasion of diseases and pests, inadequate technical know-how, inadequate credit facilities to expand production and the use of inappropriate farming practices and techniques. The objective of the study was to assess the effect of maize production on food security in Garu district of the Upper East region of Ghana. Purposive sampling technique was used to select Garu district out of the thirteen districts in the Upper East region of Ghana. The purposive sampling technique was again used to select 10 predominantly maize farming communities within the Garu district. The stratified sampling technique was used to selects respondents from the ten communities, while simple random sampling was used to select Agricultural Extension Agents for the study. In all, 124 respondents were selected for the study. The study revealed that over 50% of household members had enough maize to feed on throughout the 12 months period of the year. The study further established that most household made good use of maize as their main diet and nutrition throughout the year. It is recommended that capacity building of farmers on agronomic practices and improved modern methods of farming should be intensified to further sharping the skills of farmers for increased productivity and hence, improved food security. It is also recommended that the Department of Agriculture should ensure effective extension services delivery to increase yields of maize from the average of 4-6 100kg bags per acre to 10 bags per acre.